5-oxo-ETE activates migration of H295R adrenocortical cells via MAPK and PKC pathways - Neuman, Isabel (2019)
The OXE receptor is a GPCR activated by eicosanoids produced by the action of 5-lipoxygenase. We previously found that this membrane receptor participates in the regulation of cAMP-dependent and -independent steroidogenesis in human H295R adrenocortical carcinoma cells. In this study we analyzed the effects of the OXE receptor physiological activator 5-oxo-ETE on the growth and migration of H259R cells. While 5-oxo-ETE did not affect the growth of H295R cells, overexpression of OXE receptor caused an increase in cell proliferation, which was further increased by 5-oxo-ETE and blocked by 5-lipoxygenase inhibition. 5-oxo-ETE increased the migratory capacity of H295R cells in wound healing assays, but it did not induce the production of metalloproteases MMP-1, MMP-2, MMP-9 and MMP-10. The pro-migratory effect of 5-oxo-ETE was reduced by pharmacological inhibition of the MEK/ERK1/2, p38 and PKC pathways. 5-oxo-ETE caused significant activation of ERK and p38. ERK activation by the eicosanoid was reduced by the “pan” PKC inhibitor GF109203X but not by the classical PKC inhibitor Gö6976, suggesting the involvement of novel PKCs in this effect. Although H295R cells display detectable phosphorylation of Ser299 in PKCδ, a readout for the activation of this novel PKC, treatment with 5-oxo-ETE per se was unable to induce additional PKCδ activation. Our results revealed signaling effectors activated by 5-oxo-ETE in H295R cells and may have significant implications for our understanding of OXE receptor in adrenocortical cell pathophysiology.